Chronological Order for Qur’anic Hermeneutics: Al-Tafsīr al-Ḥadīth of ʻIzzat Darwaza - Saenong, Farid F. (Universitas Islam Internasional Indonesia, 2025)
This paper analyzes the methodological stakes of interpreting the Qur’ān through tartīb tanzīlī/tartīb al-nuzūl (chronological order of revelation) by examining ‘Izzat Darwaza’s al-Tafsīr al-Ḥadīth and the hermeneutical “value added” created by sequencing sūras along the arc of revelation rather than the canonical muṣḥafī/tawqīfī order. It argues that Darwaza’s project reconfigures Qur’ānic interpretation into a developmental narrative of guidance tracking how themes, ethical demands, and communal norms unfold across the Meccan and Medinan phases and thereby offers an alternative map for relating Qur’ānic meaning to sīra, socio-political change, and the formation of law. Methodologically, the study combines intellectual-contextual framing with close reading of Darwaza’s stated textual decisions and interpretive patterns. It notes his adoption of an Egyptian standard chronology mediated through the Kadirgali muṣḥaf tradition (with selective departures, such as beginning with al-Fātiḥa). The analysis highlights signature features of Darwaza’s chronological hermeneutics. They include a consistent “verse-in-revelation-context” orientation that treats asbāb al-nuzūl and historical circumstance as primary interpretive variables, selective deployment of ḥadīth/riwāyāt to reinforce contextual meaning rather than to foreclose semantic development, and coherence-seeking treatment of tension and abrogation claims, including stage-specific readings of conflict verses vis-à-vis earlier proclamations of religious coexistence. This paper concludes that Darwaza’s approach yields strong benefits for historical-thematic coherence, clarifies gradual moral–legal formation, and provides a pedagogically powerful “learning curve” for modern audiences. At the same time, it stresses inherent constraints as chronological lists are not universally agreed. Its heavy reliance on socio-historical reconstruction can invite historicism and reduce engagement with micro-linguistic debates central to other tafsīr genres.